A comparative investigation on strain induced crystallization for graphene and carbon nanotubes filled natural rubber composites - D. H. Fu; Y. H. Zhan; N. Yan; H. S. Xia (eXPRESS Polymer Letters, 2015)
Natural rubber containing graphene and carbon nanotubes (CNTs) composites were prepared by ultrasonicallyassisted latex mixing. Natural rubber filled by both graphene and CNTs show significant enhanced tensile strength, while graphene exhibits a better reinforcing effect than CNTs. Strain-induced crystallization in natural rubber composites during stretching was determined by synchrotron wide-angle X-ray diffraction. With the addition of CNTs or graphene, the crystallization for natural rubber occurs at a lower strain compared to unfilled natural rubber, and the strain amplification effects were observed. The incorporation of graphene results in a faster strain-induced crystallization rate and a higher crystallinity compared to CNTs. The entanglement-bound rubber tube model was used to analyze the chain network structure and determine the network parameters of composites. The results show that the addition of graphene or CNTs has an influence on the molecular network structure and improves the contribution of entanglement to the conformational constraint, while graphene has a more marked effect than CNTs.